Alpha-lipoic acid ameliorates nab-paclitaxel-induced peripheral neuropathy by inhibiting IL-17 signaling pathway - Sun, Hong; Cai, Yuxin; Li, Ling; Xin, Xiu; Yan, Jingchao; Huang, Taomin (Frontiers in Immunology, 2025)
BackgroundThe precise mechanisms by which alpha-lipoic acid (LA) alleviates nab-paclitaxel (nab-PTX)-induced peripheral neuropathy have yet to be fully elucidated. The objective of this study was to investigate the mechanisms underlying the neuroprotective effects of LA in mitigating nab-PTX-induced peripheral neuropathy.MethodsWe established a rat model of nab-PTX-induced peripheral neuropathy to evaluate the efficacy of LA. To systematically elucidate the mechanisms by which LA alleviates nab-PTX-induced peripheral neuropathy, we utilized an integrated approach that combined network toxicology and network pharmacology. Subsequently, molecular docking analysis was performed to assess the binding affinity of the LA to the target proteins involved in the key signaling pathway. Furthermore, experimental validation was conducted to confirm the role of the key signaling pathway in the neuroprotective mechanism of LA.ResultsLA was demonstrated to effectively alleviate nab-PTX-induced peripheral neuropathy. The network analysis indicated that LA ameliorated nab-PTX-induced peripheral neuropathy primarily through the AGE-RAGE signaling pathway in diabetic complications, IL-17 signaling pathway, fluid shear stress and atherosclerosis, NOD-like receptor signaling pathway, and pathways of neurodegeneration - multiple diseases. The molecular docking indicated a potential impact of LA on the IL-17 signaling pathway. Further experiment validation revealed that nab-PTX activated the IL-17 signaling pathway, whereas LA could mitigate nab-PTX-induced peripheral neuropathy by inhibiting this pathway.ConclusionBy integrating network toxicology analysis, network pharmacology analysis, and experimental validation, this study provides a clearer understanding of the mechanisms by which LA ameliorates nab-PTX-induced peripheral neuropathy.